Insights into the mechanism of tar reforming using biochar as a catalyst - Liu, Y.; Paskevicius, Mark; Wang, H.; Parkinson, G.; Wei, J.; Asif Akhtar, M.; Li, Chun-Zhu (ELSEVIER SCI LTD, 2021)
Biochar is an efficient catalyst for tar removal from syngas during biomass gasification. The aim of this research is to investigate the mechanism of tar reforming using biochar as a catalyst. A series of in situ steam tar reforming experiments were carried out using a two-stage fluidized-bed/fixed-bed reactor at 800 °C. Mallee wood biochar (106–250 μm) was activated in 15 vol% H2O balanced with Ar for different times (0–50 min) and then used as a catalyst for tar reforming. The on-line gas composition, light tar composition and the pore structure of biochar were analysed using mass spectrometer (MS), GC–MS and synchrotron small angle X-ray scattering (SAXS) respectively. An increased ratio of H2/CO was observed after reforming with biochar compared to reforming without biochar. The destruction of light tar compounds, especially the non-oxygen-containing compounds, was significantly enhanced when activated biochars were used. Steam activation increased the specific surface area (SSA), micro- and mesopore volumes in biochar while the values stayed almost unchanged during tar reforming. Results indicate that the micro- and mesopores in biochar promote the diffusion of both small and large tar molecules into the internal surface of biochar. However, the catalytic activity of biochar for tar reforming mainly depends on the content of O-containing functional groups in biochar. The O-containing functional groups facilitate the dissociation of tar molecules to form tar radicals, giving rise to the enhanced tar removal efficiency. Moreover, the formation of tar radicals over O-containing functional groups appears as the rate-limiting step in the process of catalytic reforming of tar over biochar catalysts.